The risk of developing psoriasis in alcohol-dependent patients and possible therapeutic strategies - Iga Dudek; Dorota Sokół; Tomasz Skubel; Michał Dobrzyński; Małgorzata Drozd; Jakub Czarnota; Alicja Forma; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
Excessive alcohol consumption significantly contributes to the damage of the nervous, cardiovascular and digestive systems. According to the latest scientific reports, excessive ethanol consumption might also contribute to an increased risk of developing skin diseases such as rosacea, porphyria cutanea tarda or psoriasis. The risk of developing psoriasis in alcohol-dependent patients is estimated at 3.1-3.4%. Among these people, in addition to the use of traditional therapeutic strategies, therapy with drugs acting on the neurotransmitter systems may constitute a potential treatment. Chronic alcohol consumption increases the activation of T lymphocytes as well as the level of tumor necrosis factor-α (TNF-α) and also stimulates the excessive proliferation of keratinocytes. These factors dysregulate the immune system, predisposing to the risk of developing psoriasis. Alcohol also interferes with signaling through neurotransmission affecting dopaminergic and serotonergic systems, which may affect the immune processes in the pathogenesis of psoriasis. The results of the research showed that the daily consumption of alcohol in an amount greater than 80 grams significantly reduces the effectiveness of treatment in psoriatic patients. Moreover, traditional drugs used in the course of psoriasis (retinoids, methotrexate, cyclosporine) may show reduced activity or even lead to toxic side effects (liver fibrosis) if alcohol is not discontinued during therapy. Treatment of psoriatic patients and coexisting alcohol dependence is a separate therapeutic problem. In addition to traditional methods, drugs that affect the neurotransmitter system may become a chance, mainly due to the influence of alcohol on these systems and modulation of the immune response, which is important in the development of psoriasis.